The Accountability of Regional Financial Management A mid Covid-19 Pandemics (Study at Riau Province Government) - Annie Mustika Putri; Dian Puji Puspita Sari (Politeknik Negeri Bengkalis, 2021)
This research aims to identify the factors that influence the accountability of regional financial management amid pandemics. Specifically, this research is focused on the influence of internal control systems, and financial report accessibility towards the accountability of regional financial management amid the pandemics of Covid-19. 87 government’s employees of Riau Province are involved as samples, who are directly elaborated in regional financial report management, namely Head of Department/Agency, Head of Sub-Division in Financial, Head of Sub-Division in Program, Planning, and Report. Primary data, in the form of research respondent’s perceptions (subject) through survey, are required for research data. Data collection employs a direct survey with a questionnaire as the selected instrument. The quantitative method is utilized as the research method. For data analysis, Statistical Product and Service Solutions (SPSS) Version 25 is used. Based on the result of the research, it is revealed that the internal control system and financial reports accessibility, partially have a positive and significant influence on the accountability of regional financial management.